Provincial export cost implications of the EU Carbon Border Adjustment Mechanism on China’s metal industry - Xunzhang Pan; Xin Gao; Tianpeng Wang; Wei Xiong; Tianming Shao; Meng Li; Xuan Ye; Lining Wang; Hailin Wang; Jun Pang (iScience)
Summary: China’s exports of iron and steel, aluminum, and their products (ISAP) are significantly affected by the European Union (EU) Carbon Border Adjustment Mechanism (CBAM). This study introduces a modeling framework coupling a global multi-regional input-output table and the integrated assessment model GCAM-China, both of which embed Chinese provinces, to dynamically assess provincial cost implications of CBAM for China’s ISAP exports, considering China’s upcoming 2035 Nationally Determined Contributions. By 2034, direct emissions from China’s ISAP exports to the EU reach 5.4 MtCO2, with CBAM costs of €1,157 million. Including indirect power use raises exports to 7.4 MtCO2 and €1,572 million. Accounting for supply chain emissions yields 15.8 MtCO2 and €3,378 million. Over 65% of these costs fall on Hebei, Jiangsu, Shanxi, Liaoning, and Zhejiang. Ambitious 2035 mitigation could substantially reduce CBAM costs, with about 45% of incremental costs for accelerating electric arc furnace penetration potentially offset by avoided CBAM costs.